2008
DOI: 10.2135/cropsci2007.11.0641
|View full text |Cite
|
Sign up to set email alerts
|

Global Genetic Diversity of the Perennial Ryegrass Fungal Endophyte Neotyphodium lolii

Abstract: The symbiotic association between perennial ryegrass (Lolium perenne L.) and the fungal endophyte Neotyphodium lolii is associated with host‐specific adaptations, particularly in response to abiotic and biotic stresses. Knowledge of the origin of the symbiosis and the contribution of endophyte genotype to host phenotypic variation is currently limited. Simple sequence repeat (SSR) markers were used to assess endophyte genetic diversity in a globally distributed collection of perennial ryegrass accessions. Cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 71 publications
0
24
0
Order By: Relevance
“…The uniqueness of the present study lies in the use of endophyte‐infected seed sources from wild host populations from the native range in the Mediterranean region where L. perenne (and Neotyphodium lolii ?) probably originated (Wilson, 1996; Balfourier et al, 1998; van Zijll de Jong et al, 2008). Growth and reproduction of these foreign populations in two unmanaged gardens in New Jersey, United States were compared to that of two infected cultivars developed from locally available plants for use in the northeastern United States (Hurley et al, 1994a, b).…”
Section: Discussionmentioning
confidence: 99%
“…The uniqueness of the present study lies in the use of endophyte‐infected seed sources from wild host populations from the native range in the Mediterranean region where L. perenne (and Neotyphodium lolii ?) probably originated (Wilson, 1996; Balfourier et al, 1998; van Zijll de Jong et al, 2008). Growth and reproduction of these foreign populations in two unmanaged gardens in New Jersey, United States were compared to that of two infected cultivars developed from locally available plants for use in the northeastern United States (Hurley et al, 1994a, b).…”
Section: Discussionmentioning
confidence: 99%
“…The perennial ryegrass genomic DNA-derived SSR marker LPSSRK03A02 ( Jones et al, 2001) was included as a positive control for effi ciency of amplifi cation from purifi ed DNA. Polymerase chain reaction (PCR) amplifi cation was performed in a 20 μL reaction following the protocol of van Zijll de Jong et al (2008a). Cycling conditions for each reaction consisted of 10 min at 95°C followed by 10 cycles of 30 s at 94°C, 60 s at the initial annealing temperature (reducing the temperature at 1°C per cycle), and 1 min at 72°C followed by 20 cycles of 30 s at 94°C, 60 s at the fi nal annealing temperature, and 1 min at 72°C followed by a fi nal extension of 10 min at 72°C.…”
Section: Detection Of Endophyte-positive Accessionsmentioning
confidence: 99%
“…A comprehensive set of simple sequence repeat (SSR) markers was developed from genic sequences of Neotyphodium species (van Zijll de Jong et al, 2003) and was demonstrated to detect orthologous sequences across a broad range of Neotyphodium and Epichloë species. Formatting of marker subsets for in planta detection permitted analysis of global genetic diversity among endophytes (predominantly Neotyphodium lolii) of perennial ryegrass (Lolium perenne L.) and revealed signifi cant correlations between SSR genotype and alkaloid-based metabolic profi le (van Zijll de Jong et al, 2008a). In addition, SSR profi ling permitted discrimination of novel favorable endophyte genotypes and quality assurance of the incidence of such strains in commercial breeding programs (van Zijll de Jong et al, 2008b).…”
mentioning
confidence: 99%
“…Here, four distinct, endophyte‐infected cultivars (Palmer II, Prelude II, Repell II, and Yorktown III) were used to supply the genotypes in an effort to maximize the available genotypic variation in morphological traits that could differentially respond to both competition and endophyte infection. Note that it is not known to what extent there may have been genetic variation in the clavicipitaceous endophytes that occupied the different host genotypes and cultivars, although molecular genetic variation in the asexual endophyte of perennial ryegrass is limited due to the absence of sexual reproduction (van Zijll de Jong et al, 2008).…”
Section: Methodsmentioning
confidence: 99%